Dissolution of non-functionalized and functionalized nanomaterials in simulated biological and environmental fluids - Mbanga, Odwa (University of the Witwatersrand, Johannesburg, 2023)
The incorporation of nanoparticles in consumer products is exponentially high, however, research into their behaviour in biological and environmental surroundings is still very limited. In the present study, the static system and the continuous flow-through dissolution protocols were utilized to evaluate and elucidate the dissolution behaviour of gold, silver, and titanium dioxide nanoparticles. The behaviour of these particles was studied in a range of artificial physiological fluids and environmental media, to obtain a more precise comprehension of how they would react in the human body and the environment. The biodurability and persistence were estimated by calculating the dissolution kinetics of the nanoparticles in artificial physiological fluids and environmental media. The details of the current research are described as follows: An investigation into the dissolution of non-functionalized and functionalized gold nanoparticles was conducted as the first component of the research, examining the effect of surface functionalization on dissolution. The study determined the dissolution rates of functionalized and non-functionalized gold nanoparticles. Dissolution was observed to be significantly higher in acidic media than in alkaline media. The nanoparticle surface modification, particle aggregation, and chemical composition of the simulated fluid significantly affected the dissolution rate. It was concluded that gold nanoparticles are biodurable and have the potential to cause long-term health effect as well as high environmental persistency. This work has been published in the Journal of Nanoparticle Research and is presented in this thesis as Paper 1. Silver nanoparticles were also included in this study because they have many applications and industrial purposes. Therefore, their risk assessment was also of utmost importance. The results indicated that silver nanoparticle solubility was influenced by the alkalinity and acidity of artificial media. Low pH values and high ionic strength encouraged silver nanoparticle dissolution and accelerated the dissolution rate. The agglomeration state and reactivity of the particles changed upon exposure to simulated fluids, though their shape remained the same. The fast dissolution rates in most fluids indicated that the release of silver ions would cause short-term effects. This work has been published in Toxicology Reports and has been presented in this thesis as Paper 2. Although titanium dioxide nanoparticles are insoluble and undergo negligible dissolution, it was of utmost importance to investigate their behaviour in biological and environmental surroundings. This is as a result of the incorporation of these particles in everyday consumer products, in the nanosized range which raises concerns about their safety. Therefore, in Paper 3 presented in this thesis the dissolution kinetics of titanium dioxide nanoparticles in simulated body fluids representative of the lungs, stomach, blood plasma and media representing the aquatic ecosystem were investigated to anticipate how they behave in vivo. This work has been published in Toxicology In Vitro and presented in this thesis as Paper 3. The results indicated that titanium dioxide nanoparticles were very insoluble, and their dissolution was limited in all simulated fluids. Acidic media such as the synthetic stomach fluids were most successful in dissolving the particles, while alkaline media had lower dissolution. High ionic strength seawater also had a higher dissolution rate than freshwater. The dissolution rates of the particles were low, and their half-times were long. The results indicated that these particles could potentially cause health issues in the long term, as well as remain unchanged in the environment. This work has been published in Toxicology In Vitro and presented in this thesis as Paper 3. The last component of the research compared the dissolution kinetics of gold, silver and titanium dioxide nanoparticles through the use of the continuous flow-through system. The findings indicated that titanium dioxide nanoparticles were the most biodurable and persistent, followed by gold and silver nanoparticles. Therefore, it was suggested that product developers should use the OECD's guidelines for testing before releasing their product to the market to ensure its safety. This work has been published in Nanomaterials MDPI and presented in this thesis as Paper 4.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of philosophy to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Dissolution; Biodurability; Persistence; Gold nanoparticles; Silver nanoparticles; Titanium dioxide nanoparticles; Dissolution kinetics; UCTD; SDG-9: Industry, innovation and infrastructure